Impact of government digital transformation on citizen trust and participation: evidence from Gowa Regency, Indonesia - Nurlinah,; Ansar, Muhammad Chaeroel; Chowdhury, Kuntala (Frontiers in Human Dynamics, 2025)
This study examines the relationship between digital transformation, trust in government, and citizen participation in Gowa Regency, Indonesia, a region marked by urban–rural disparities. Drawing on a survey of 394 respondents across urban, semi-urban, and rural districts, the research employs descriptive and inferential statistical analysis, including ordinary least squares regression, to investigate how perceptions of digital public services influence trust and participatory behaviors. Findings reveal that digital transformation significantly enhances both trust in government and participation, while trust itself emerges as a strong predictor of citizen participation. However, participation levels remain modest, highlighting a persistent gap between positive perceptions of digital services and actual civic involvement. Spatial differences further complicate the picture: urban areas report higher digital transformation and trust scores, yet participation peaks in transitional zones, suggesting complex socio-structural dynamics. These results underscore that while digital transformation can foster institutional trust, its participatory potential requires complementary strategies addressing inclusivity, literacy, and feedback mechanisms. The study contributes to debates on digital governance by demonstrating that technology alone does not guarantee democratic responsiveness, but its impact is contingent on local contexts and the mediating role of trust.